EFEKTIFITAS KOTORAN SAPI SEBAGAI AKTIFATOR PEMBUATAN BIOGAS DARI JERAMI PADI - Fajri, Nindi (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
Biogas is gas mixture yielded by bacterium of metanogenik that happened at materials able to ravelled naturally in a condition anaerobik. Target of in this research is known by time depth forming of biogas of paddy hay with ox dirt aktifator. This research is research of eksperiment by using Posttest design group control only design. This research use two data analysis that is Univariat and Bivariate. Pursuant to result of test of anoway anova research of time depth mean forming of biogas with addition of ox dirt 3 singk during 11 day, addition of ox dirt 5 singk during 9 day, and addition of ox dirt 7 time depth mean singk forming of biogas during 8 day, while time depth forming of biogas at control during 17 day with value p = 0,000 = 0,05. That there is difference having a meaning of among/between time depth forming of biogas to addition of dirt aktifator with dose of aktifator 3 singk, 5 singk, and 7 singk.